Management of Pediatric Acute Dacryocystitis. Issue 5 (26th March 2021) - Prat, Daphna; Magoon, Katie; Revere, Karen E.; Katowitz, James A.; Katowitz, William R.
Abstract : Purpose: To analyze the clinical presentation, course, and management in a large cohort of pediatric acute dacryocystitis subjects and to examine whether hospitalization and urgent surgical intervention are indeed mandatory. Methods: A retrospective analysis of all pediatric subjects diagnosed with dacryocystitis at the Children's Hospital of Philadelphia over a 12-year period (2009–2020). Results: One-hundred sixty-nine pediatric acute dacryocystitis patients were included in this study. Management included admission in 117 cases (69%). Sixty-eight patients (40%) were treated medically with no surgical intervention, 75 cases (44%) required urgent surgical intervention, and 26 additional cases (15%) required surgery due to persistent tearing symptoms after medical management. The urgent procedures included most commonly: 1) endonasal examination and microdebridement of intranasal cysts in 26 cases (35%); 2) probing and irrigation without examination and microdebridement, with or without stent intubation, in 30 cases (40%); and 3) dacryocystorhinostomy (13 endonasal and 4 external) in 17 cases (23%). Conclusions: Management of pediatric acute dacryocystitis should be tailored individually for each case. Hospital admission and early surgical intervention are not mandatory, as 31% of cases resolved without admission, and 56% without early surgical intervention. Although a specific age cutoff is not plausible, hospital admission for younger patients is more commonly advocated. When surgical intervention is indicated, endonasal examination and microdebridement of any associated intranasal cyst and probing with possible stenting are the initial procedures of choice. Dacryocystorhinostomy is reserved for more complex obstructions. Although pediatric acute dacryocystitis is an infection with serious potential problems, when managed appropriately, complications are rare. Abstract : Acute pediatric dacryocystitis can initially be managed with medical treatment alone, particularly for patients older than 1 year of age; when surgical intervention is indicated, endonasal examination is helpful to diagnose and treat associated intranasal cysts.